PENGENALAN PERMAINAN TRADISIONAL SEJAK DINI SEBAGAI PEMBENTUKAN KARAKTER ANAK DI RUMAH BELAJAR DAN BERMAIN UNTUKMU SI KECIL JEMBER - Ana Aniati (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2013)
Education through traditional games, in addition to training children to have solidarity, social sensitivity, solidarity harmonious with the surrounding environment, is also one of the efforts to preserve the local wisdom education. Foundation